2002
DOI: 10.1002/path.1043
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity and allelic imbalance in apocrine metaplasia of the breast: microdissection microsatellite analysis

Abstract: Loss of heterozygosity (LOH) and allelic imbalance (AI) at loci reported to show allele loss and/or imbalance in preinvasive and invasive breast cancer were examined in 41 cases of apocrine metaplasia (APM) of the breast using a microdissection technique, polymorphic microsatellite markers, and the polymerase chain reaction (PCR). Occasional examples of LOH and/or AI were identified in 2/28 (7.1%) informative cases at 1p (MYCL1), 2/14 (14.3%) at 11q (INT2), 1/15 (6.7%) at 13q (D13S267), 3/22 (13.6%) at 16q (D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…Up to one-third of the women aged 30 -50 years have cysts in their breasts (3), and both their frequency and their proposed association with an increased risk of breast cancer have underpinned the importance of investigating these lesions at the molecular level (53,89). In particular, apocrine changes, which span from benign metaplasias to atypical apocrine hyperplasia (12,53), have attracted much attention because apocrine epithelia may be a precursor in malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Up to one-third of the women aged 30 -50 years have cysts in their breasts (3), and both their frequency and their proposed association with an increased risk of breast cancer have underpinned the importance of investigating these lesions at the molecular level (53,89). In particular, apocrine changes, which span from benign metaplasias to atypical apocrine hyperplasia (12,53), have attracted much attention because apocrine epithelia may be a precursor in malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on morphological, immunohistochemical, and molecular findings, CCL, ADH, and well-differentiated DCIS would be unlikely candidates. Although apocrine change has long been considered a metaplastic process in breast tissues, usually associated with ageing, this concept has come into question with the application of molecular findings [2,17,[71][72][73]. At least a subset of lesions with apocrine morphology show molecular changes, including LOH/allelic imbalance at 1p (MYCL1), 11q (INT2), 13q, 16q and 17q [71,72], and recurrent chromosomal changes as defined by CGH, including loss of 1p, 2p, 10q, 16q, 17q and 22q, and gain of 1p, 2q and 13q [17].…”
Section: Hyperplasias and Columnar Cell Changementioning
confidence: 99%
“…The authors concluded that histologically more complex lesions are associated with significant increase of proliferative capacity and alterations of cell cycle control. Furthermore, comparative genomic hybridization has shown a similar pattern of molecular alterations in benign and malignant apocrine lesions [2,4], implying that some apocrine lesions without atypia might also be clonally derived. This is supported by findings of LOH and allelic imbalance in apocrine metaplasia [4].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, comparative genomic hybridization has shown a similar pattern of molecular alterations in benign and malignant apocrine lesions [2,4], implying that some apocrine lesions without atypia might also be clonally derived. This is supported by findings of LOH and allelic imbalance in apocrine metaplasia [4]. Our finding of an almost complete loss of C-KIT expression in benign apocrine lesions is consistent with an earlier report which suggests that C-KIT expression, regardless of cell type, is an indicator of potential for neoplastic transformation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation